Concept And Importance Of Detection Failureś Possibilities Of Corporation Proposed Model For Application In The Iraqi Environment - عبد الله, بشرى نجم; جواد, ضمياء محمد (Journal of Economics and Administrative Sciences, 2014)
Research aims to shed light on the concept of corporate failures , display and analysis the most distinctive models used to predicting corporate failure; with suggesting  a model to reveal the probabilities of corporate failures which including internal and external financial and non-financial indicators, A tested is made for the research objectivity and its indicators weight and by a  number of academics professionals experts, in addition to  financial analysts  and have concluded a set of conclusions ,  the most distinctive of them that failure is not considered a sudden phenomena for the company and its stakeholders , it is an Event passes through numerous stages; each have their symptoms that lead eventually to company life starting from performance deteriorating then economic failure which leads to insolvency, bankruptcy, liquidation, hence, corporate  failure could be predicted by using certain models containing a set of internal and external financial indicators in order to reach primary results that assist management in to diagnose performance strengths and weaknesses and take suitable corrective actions , of previously mentioned, recommendations have come out represent in applying the suggestive model to discover and report about the possibilities of Iraqi corporate failures to enable their management of predicting company future  periodically; as it can through  applying  this model determining its continuity elements difficulties problems facing in the future and the alternatives to overcome them, In addition this models is considered one of many  analytical procedures when evaluating the company 's ability of continuity for auditors.